PERENCANAAN AWAL DERMAGA APUNG LAKKANG - M Nur, Fahrul; Paotonan, Chairul; Assidiq, Fuad Mahfud (Riset Sains dan Teknologi Kelautan, 2024)
Lakkang is one of the neighbourhoods located in Tallo Sub-district, Makassar City and is a residential area and tourist destination purpose. Lakkang can be accessed from varius directions, namely from Kera-kera and Tallo. To get to Lakkang, people currently use catamaran boats. In order to support shipping to Lakkang, a pier was built on the island called the Lakkang pier. Lakkang Pier is made of wood. The existing pier at this time during the high tide season with flood discharge the pier is submerged in water, the distance between the pier floor and the low tide elevation is 1.93 m and the condition of the pier construction is not safe for the process of loading and unloading goods and getting on and off passengers. Therefore, a pier design is needed that can overcome these problems. The purpose of this research is to conduct preliminary planning of floating docks in Lakkang. The research starts from collecting secondary data and primary data. Secondary data includes spatial planning documents, social economy and river discharge. While primary data include tides, bathymetry, shipload, and ship data. Furthermore, analysis of all data collected was carried out to determine the dimensions of the floating dock. The planning results obtained the dimensions of the planned pier have a length of 9.2 m, a width of 5.2 m, a height of 0.708 m, and a ladder of 0.115 m.